Music of the heart - Craven, Wes; Streep, Meryl; Quinn, Aidan; Estefan, Gloria; Bassett, Angela (Craven-Maddalena Films, 2000)
The true story of a young teacher who fights against the board of education in her bid to teach underprivileged kids in a Harlem school the beauty of music through the violin. In her struggle she loses everything as the system comes down on her with all their might but her determination for the kids happiness helps her to battle back with wonderfully inspirational results.